The structure of social representation of death in the interface with the religiosities of healthcare professionals groups / A estrutura da representação social da morte na interface com as religiosidades em equipes multiprofissionais de saúde - Alexsandro Medeiros do Nascimento; Antonio Roazzi (Psicologia: Reflexão e Crítica, 2007)
The study aims to investigate the structure of social representation of death in a Healthcare professional group establishing an interface with religiosity and how the latter interferes in the meaning attributed to death by this specific population. Open and closed questions on death or the act of dying, and on the singular religious experience of the participants were applied. Written protocols were collected from a sample of 80 professionals (49 physicians, 13 psychologists, and 18 nurses), which were analyzed according to content analysis and non-metric multidimensional analysis, SSA (Similarity Structure Analysis), and interpreted according to the theory of Social Representations, revealing a significant interference of religious believes in the structure of death representation.